Delivery of Poorly Soluble Drugs via Mesoporous Silica: Impact of Drug Overloading on Release and Thermal Profiles - Tuan-Tu Le; Abdul Khaliq Elzhry Elyafi; Afzal R. Mohammed; Ali Al-Khattawi (MDPI AG, 2019)
Among the many methods available for solubility enhancement, mesoporous carriers are generating significant industrial interest. Owing to the spatial confinement of drug molecules within the mesopore network, low solubility crystalline drugs can be converted into their amorphous counterparts, which exhibit higher solubility. This work aims to understand the impact of drug overloading, i.e., above theoretical monolayer surface coverage, within mesoporous silica on the release behaviour and the thermal properties of loaded drugs. The study also looks at the inclusion of hypromellose acetate succinate (HPMCAS) to improve amorphisation. Various techniques including DSC, TGA, SEM, assay and dissolution were employed to investigate critical formulation factors of drug-loaded mesoporous silica prepared at drug loads of 100−300% of monolayer surface coverage, i.e., monolayer, double layer and triple layer coverage. A significant improvement in the dissolution of both Felodipine and Furosemide was obtained (96.4% and 96.2%, respectively). However, incomplete drug release was also observed at low drug load in both drugs, possibly due to a reversible adsorption to mesoporous silica. The addition of a polymeric precipitation inhibitor HPMCAS to mesoporous silica did not promote amorphisation. In fact, a partial coating of HPMCAS was observed on the exterior surface of mesoporous silica particles, which resulted in slower release for both drugs.